Relation entre la perception de l`effort au seuil d`oxydation maximale des lipides (LIPOXmax), les réponses physiologiques et le profil psychologique de cyclistes compétiteurs - Coquart, J.B.J.; Grosbois, J.-M.; Nycz, M.; Dufour, Y.; Bart, F.; Garcin, M. (Science & Sports, 2012)
Objective The objective was to examine the relationship between rating of perceived exertion (RPE) at the point of maximal lipids oxidation (LIPOXmax), physiological responses and psychological profile in trained competitive cyclists. Patients and methods Twenty-one competitive cyclists performed an exercise test in order to determine RPE at LIPOXmax. During this exercise test, physiological responses at LIPOXmax were measured. Moreover, a psychological profile for each cyclist has been evaluated from questionnaires (levels of anxiety, desire for success, self-esteem, psychological resistance and endurance, dynamism, competitiveness, activity control, risk-taking, emotional control, extroversion-introversion, leadership, aggressiveness, sociability, cooperation, acceptance of a judgment, and social desirability). Multiple linear regression analysis was performed to determine the physiological and psychological factors linked to RPE at LIPOXmax. Results Only the percentage of maximal oxygen uptake (VO2max), leadership and psychological endurance explained significantly the RPE at LIPOXmax. Conclusion More the cyclists have a low RPE at LIPOXmax, more their LIPOXmax (in % VO2max ) was low. Cyclists with high level of leadership (i.e., persuasive, with command ability) and/or psychological endurance (i.e., persistent, obstinate) have lower RPE at LIPOXmax than the cyclists with lower level of leadership and/or psychological endurance.